2010
DOI: 10.1111/j.1532-7795.2010.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and Alcohol Use in Early Adolescence: A Multilevel Social Network Approach

Abstract: This study applies multilevel social network analytic techniques to examine processes of homophilic selection and social influence related to alcohol use among friends in early adolescence. Participants included 3,041 Dutch youth (M age =12 years, 49% female) from 120 classrooms in 14 schools. Three waves with 3‐month intervals of friendship nomination data and self‐reports of drinking behavior were collected. Results revealed that within classrooms, friendship nominations tended to be reciprocated and dyadic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
132
5
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 38 publications
10
132
5
6
Order By: Relevance
“…Afterschool networks may differ from other childhood friendship networks. We found that afterschool networks have a notably lower tendency toward reciprocity (OR = 1.99, P , .01) in comparison with most childhood friendship networks reported in the social network literature (OR = 7.4 23,25,26 ). Despite this structural difference between afterschool networks and other childhood friendship networks, we found significant effects that are of real world importance, because many afterschool programs are trying to increase physical activity to meet state-level guidelines.…”
Section: Sample Size and Compositioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Afterschool networks may differ from other childhood friendship networks. We found that afterschool networks have a notably lower tendency toward reciprocity (OR = 1.99, P , .01) in comparison with most childhood friendship networks reported in the social network literature (OR = 7.4 23,25,26 ). Despite this structural difference between afterschool networks and other childhood friendship networks, we found significant effects that are of real world importance, because many afterschool programs are trying to increase physical activity to meet state-level guidelines.…”
Section: Sample Size and Compositioncontrasting
confidence: 39%
“…[23][24][25][26] Through the use of newly developed stochastic actor-based models, these studies have been able to disentangle the complicated interplay between friendship selection (along lines of visible health behaviors) and behavioral influence (due to social ties). In this study, we extended such actor-based models to the study of the coevolution of friendship networks and physical activity.…”
mentioning
confidence: 99%
“…Research also indicates that early-onset drinking can be socially reinforced through peers. For example, Knecht et al (2011) documented that as adolescents drink more over time, they gain more friends who drink similarly. Simons-Morton and Chen (2006) documented that this relationship works the other way as well: as an adolescent gains more friends who drink, the adolescent will start to drink more alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Knecht et al (2011) use directed 'best friend' nominations, while we use various combinations of network variables, including 'best friend' nominations but also measures of spending leisure time together and discussing personal matters. Given these differences, it is not clear how the differences in findings should be judged.…”
Section: Discussionmentioning
confidence: 99%